Atribut Mutu Keripik Pisang Masak dengan Menggunakan Metode Importance Performance Analysis (IPA) - Citra Resmi Hayuningtyas; Bambang Herry Purnomo; Nurhayati Nurhayati (Jurnal Mutu Pangan : Indonesian Journal of Food Quality, 2022)
The food processing industry currently produces various kinds of products with local food brands. In Lumajang Regency, the availability of banana var. Mas Kirana (Musa acuminate 'lady Finger') is very abundant so that it provides significant business opportunities. This study determined the quality attributes of ripe banana chips from SMEs in Lumajang Regency. Questionnaires were distributed to 100 respondents. The results of the questionnaire were processed using the Importance Performance Analysis (IPA) method. The results showed that the quality attributes of ripe banana chips based on the IPA method were ease of breaking, taste stability, packaging information, packaging safety, and shelf life. The key attributes of the "Freezing" brand were the ease of breaking attribute (3.90), taste stability attribute (3.86) and packaging safety attribute (3.97). The key attributes of the burno sari brand were the taste attributes (3.94), and packaging information attributes (3.83). The key attribute of the "Kurnia" brand was the taste attribute. It means that (3.94). This means that all brands sampled on ripe banana chips products have good quality (satisfying consumers) with certain attribute that stand out in each brand.